2021
DOI: 10.3390/biology10121310
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Binding of Receptor-Binding Domain (RBD) of SARS-CoV-2 Wild Type and B.1.620 Variant with hACE2 Using Molecular Docking and Simulation Approaches

Abstract: Recently, a new variant, B.1620, with mutations (S477N-E484K) in the spike protein’s receptor-binding domain (RBD) has been reported in Europe. In order to design therapeutic strategies suitable for B.1.620, further studies are required. A detailed investigation of the structural features and variations caused by these substitutions, that is, a molecular level investigation, is essential to uncover the role of these changes. To determine whether and how the binding affinity of ACE2–RBD is affected, we used pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…On the other hand, the binding of some compound to the RBD-ACE2 complex could block the virus spread. 43 Additionally, some pyrazolones were identified as potent inhibitors of angiotensin-converting enzyme (ACE), which has a number of pathological roles. 44 This prompted us to investigate the binding of selected pyrazolones to human ACE2 cell receptors, as well as to the spike RBD-ACE2 complex, with the idea that in such case, the SARS-CoV-2 cell entry and spreading could also be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the binding of some compound to the RBD-ACE2 complex could block the virus spread. 43 Additionally, some pyrazolones were identified as potent inhibitors of angiotensin-converting enzyme (ACE), which has a number of pathological roles. 44 This prompted us to investigate the binding of selected pyrazolones to human ACE2 cell receptors, as well as to the spike RBD-ACE2 complex, with the idea that in such case, the SARS-CoV-2 cell entry and spreading could also be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of tighter binding of the SARS-CoV-2 S-protein was studied by using MD simulations and MM/GBSA or MM/PBSA calculations by Xue et al, Jafary et al, Spinello et al., and Bhattacharyya et al Interestingly, MM/PBSA calculations at different temperatures suggested that the SARS-CoV-2 RBD was more resistant to temperature changes than the SARS-CoV RBD . Researchers ran MM/PBSA calculations and found that some mutations on S protein could facilitate stronger interactions with human ACE2. …”
Section: Methods and Approachesmentioning
confidence: 99%
“…The network analysis focuses on studies with applications in cancer research( 15 ). A molecular docking study could be employed to evaluate the PDI network( 16 ). In 2017, Zeeshan Yousuf et al .…”
Section: Introductionmentioning
confidence: 99%